Penerapan Sistem Tertanam untuk Monitoring Kandang Ayam Broiler - Fathurrahmani Fathurrahmani; Wiwik Kusrini; Khairul Anwar Hafizd; Arif Supriyanto (Universitas Bumigora, 2019)
Broilers are fast growing animals that are influenced by environmental conditions. Routine monitoring is needed, especially temperature, humidity and ammonia levels. In this study, the authors propose an embedded system that can detect temperature, humidity and ammonia levels. This system works by sending temperature, humidity and ammonia gas information routinely once a day to the henhouse operator via text message (SMS), or information will be sent if environmental conditions are above/below the threshold. The embedded system was built using microcontrollers, temperature and humidity sensors as well as ammonia sensors. The microcontroller uses Arduino. Temperature and humidity sensors use DHT11, while the ammonia level sensor uses MQ-135. Embedded system communication uses the GSM SIM800L module, this module is responsible for sending the henhouse environmental conditions to the operator via SMS. Testing is done in two stages, namely functionality and connectivity. The functionality test proves that the sensor can produce information on temperature, humidity and ammonia levels by comparing it with conventional tools. The connectivity test proves that the GSM SIM800L module can send monitoring data every day and certain conditions.